1979
DOI: 10.1530/jrf.0.0560439
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of carnitine and acetylcarnitine in the rabbit epididymis and the carnitine content of rabbit spermatozoa during maturation

Abstract: The highest levels of carnitine and acetylcarnitine were found in the cauda, and spermatozoa from the proximal cauda contained significantly greater amounts of carnitine than those removed from the corpus or caput epididymidis. Acetylcarnitine levels (as a % of the total carnitine pool) were greater in all regions of the rabbit epididymis than has been reported in other species. It is suggested that the accumulation of carnitine is involved in sperm maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
2

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
3
13
0
2
Order By: Relevance
“…The present results support our hypothesis that the accumulation of carnitine is one aspect of sperm maturation in the rabbit (Casillas & Chaipayungpan, 1979). For the most part, we used the culture system described by Orgebin-Crist & Tichenor (1973) and Orgebin-Crist & Jahad (1978) who have demonstrated that spermatozoa maintained in culture tubules from the proximal corpus epididymidis develop the ability to fertilize ova only when androgen is added to the medium.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present results support our hypothesis that the accumulation of carnitine is one aspect of sperm maturation in the rabbit (Casillas & Chaipayungpan, 1979). For the most part, we used the culture system described by Orgebin-Crist & Tichenor (1973) and Orgebin-Crist & Jahad (1978) who have demonstrated that spermatozoa maintained in culture tubules from the proximal corpus epididymidis develop the ability to fertilize ova only when androgen is added to the medium.…”
Section: Discussionsupporting
confidence: 88%
“…Carnitine accumulates in bovine (Casillas, 1973) and in rabbit (Casillas & Chaipayungpan, 1979) spermatozoa as they mature in the epididymis and we have suggested that one of the functions of the organ is to supply carnitine to spermatozoa as they mature. We have also presented evidence that carnitine plays a special role in the metabolism of mature bovine and monkey spermatozoa (Casillas & Erickson, 1975a).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…L'épididyme est l'un des organes où la concentration de carnitine est la plus élevée (Marquis et Fritz, 1965b ;Casillas, 1972 ;Brooks, 1980 (Casillas, 1972(Casillas, , 1973 Chaipayungpan, 1979 ;Inskeep et Hammerstedt, 1982 ;Casillas et al, 1984 (Hinton et al, 1979 ; Chaipayungpan, 1979 ;Casillas et al, 1984). Les Chaipayungpan, 1979 ;Casillas et al, 1984).…”
unclassified
“…Les Chaipayungpan, 1979 ;Casillas et al, 1984). L'acétylcarnitine du plasma séminal humain n'est pas d'origine épididy-maire et n'est pas un produit du métabolisme des spermatozoïdes (Soufir et Jeulin, 1985 (Hinton et al, 1979;Casillas, 1973; Chaipayungpan, 1979 ;Casillas et al, 1984).…”
unclassified